The influence of the Gonads on Protein Metabolism - Schrire, I (Division of Physiological Sciences, 2020)
It has long been known that the gonads exercise an important effect on the individual, nut only in recent years has it been recognized how intricate and vast this effect can be. From the earliest of times it was common knowledge that gonadectomy in either males or females resulted in sterility. Associated with this sterility were several well marked physical and mental changes, as represented by the non-appearance of the secondary sexual characters, which were shown ti be dependent on the internal secretions of the gonads. The nature of these secondary sexual characters is well-known and the changed in the individual are detailed in all text books of physiology. But the effects produced by these internal secretions have since been shown to be far more complicated involved than had hitherto been thought.